A lecture on landslides: Physical and numerical modelling of large ground movements - Ooi, Teik Aun, Ir. Dr.; Hisham, Mohamad, Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.